Circular Economy for Sustainable Steel Structure - Dian Laras Wati; Oei Fuk Jin (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Steel construction contributes significantly to global carbon emissions and energy consumption. In response to sustainability concerns, circular economy principles offer a promising approach to reducing waste, maximizing material reuse, and minimizing environmental impact. This study presents a systematic literature review of 317 Scopus-indexed articles published between 2010 and 2024. The selection focused on reputable journals (Q1–Q4), environmentally friendly steel structures, reuse, and life cycle assessment (LCA). Bibliometric and keyword mapping analysis using VOSviewer revealed that the topic of steel structure reuse and sustainability is still fragmented. Design for Deconstruction (DfD) practices were found to reduce emissions by up to 70% compared to new structures but face practical limitations due to technical and economic challenges. Moreover, the reuse of industrial by-products such as steel slag and blast furnace gas shows high potential for energy savings and CO₂ reduction, although adoption remains limited. These findings highlight the need for innovative joint design, technological integration, and policy incentives to advance circular economy implementation in steel construction.